Control de potencia activa y reactiva en sistemas de generación eólica usando una máquina de inducción doblemente alimentada. - Iván Paúl, Cayo Pallasco (2020)
The present research work arises due to the double-fed induction wind turbines cannot deliver a stable active and reactive power, because of the disturbances that occur with the wind variation, causing they cannot be connected to the grid directly, Therefore, a control of active and reactive power in wind power generation systems is modeled using a double-feed machine, which firstly starts from the analysis of different bibliographic sources in order to broaden and deepen different approaches, theories, opinions and recommendations of the different authors, as well as to identify the variables which are going to be controlled. For the research, the type 3 wind turbine is chosen, which is based on a double-fed variable speed induction generator where the stator is directly connected to the grid and the rotor is connected to the grid through an AC-DC-AC converter. As a result, the vector control method was implemented for decoupled control of active and reactive power, which is modeled and implemented with the Matlab/ Simulink software. The complete model includes general turbine aerodynamics, mechanical drive train, DFIG, current-regulated power converters and the wind turbine control system, where a maximum power point tracker (MPPT) was designed, for the extraction of maximum wind power, The PLL control is in charge of synchronizing the phase angle with the voltage and provides stability and perturbation rejection to the angle estimation, OUTHER LOOP and INNER LOOP controls are in charge of obtaining the Id and Iq currents, also the normal and inverse CLARK and PARK Transforms to change the reference systems, and finally a PWM block in charge of sending the pulses to the converters. With the type of control implemented, it is possible to inject active and reactive power into the bar infinite with a power factor close to the unit. In addition, it is possible to demonstrate the effectiveness of this control by delivering approximately 1.9 MW of active power, which is superior to Matlab's "Wind Farm - DFIG Detailed Model" example, which delivers 1.5 MW due to the different power electronics presented in the example.